PENETAPAN KADAR AKRILAMIDA PADA MAKANAN HEWANI DAN NABATI PANGGANG DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Sofia Eliasari Br Bangun; Sulasmi Sulasmi; Masria Phetheresia Sianipar (Jurnal Penelitian Farmasi & Herbal, 2026)
This study aimed to determine the acrylamide levels in animal-based (grilled chicken and grilled fish) and plant-based (grilled Cilembu sweet potato) foods using the UV-Vis spectrophotometry method. Acrylamide is a carcinogenic compound formed in foods heated to high temperatures. The samples were tested qualitatively and quantitatively. Qualitative tests confirmed the presence of acrylamide in all three samples. Quantitative measurement was performed at a maximum wavelength of 267 nm and showed the average acrylamide levels in grilled Cilembu sweet potato, grilled chicken, and grilled fish were 51.3964 mcg/g, 38.1875 mcg/g, and 32.1383 mcg/g, respectively. The highest level was found in the grilled Cilembu sweet potato due to its higher carbohydrate content. Although the detected levels are below the daily toxic limit set by BPOM, excessive long-term consumption is not recommended. The method validation test showed results that met the requirements for linearity (r = 0.995) , accuracy (recovery range 101.58% - 106.33%) , and precision (RSD < 2%) , with LOD and LOQ values of 0.4111 and 1.3703, respectively. It was concluded that the UV-Vis spectrophotometry method is effective for the analysis of acrylamide in grilled food samples.